Distant antecedents of psychotherapy in mental health - Valenzuela Romero, Alex Alfredo (2022)
Sigmund Freud, the father of psychoanalysis, is one of the most controversial and influential characters of the twentieth century. Therefore, the impact of their controversial and revolutionary ideas transcends to this day, not just in the various professional schools of Psychology in Peru and the world, but in everyday life. His theoretical contributions expanded the knowledge of the psychological problems of man and transcended each of the spheres of human knowledge and work. Therefore, terms such as unconscious, repression, transfer, defense mechanism, etc., are found in the popular vocabulary. Even many people are convinced that psychoanalysis is synonymous with psychology. Psychoanalysis in addition to a psychotherapeutic current, for many people, has become a form and philosophy of life. However, the origin of psychotherapy is unknown, a problem that in this article intends to analyze.